The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1590/1806-9061-2017-0495
|View full text |Cite
|
Sign up to set email alerts
|

Improving Nutrition Utilization and Meat Quality of Broiler Chickens Through Solid-State Fermentation of Agricultural By-Products by Aureobasidium Pullulans

Abstract: Mushroom stalk residue, soybean hull, Aureobasidium pullulans, digestibility, meat water holding capacity.Submitted: 21/February/2017 Approved: 28/July/2017 ABSTRACT A 35 d trial was conducted to evaluate the effects of dietary supplementation of co-fermented agricultural by-products, soybean hulls and Pleurotus eryngii stalk residue (PESR), with Aureobasidium pullulans on nutrients digestibility and meat quality in broilers fed on conventional corn-soybean meal basal diet. A total of 400 1-d-old Ross broilers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Molette et al [42] reveal that the liver is responsible to the production of a significant amount (85%) of fat in the growing birds, and highfat content in the feed tempt to increase the weight of the liver in birds. In the current experiment, there was no significant difference (p < 0.05) in liver weight between all the groups, which is consistent with Lee et al [39], proposing that the addition of fermented feed ingredients into the broiler feed will preserve the normal immunity and health levels of the birds while preventing undesirable effects on the meat.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Molette et al [42] reveal that the liver is responsible to the production of a significant amount (85%) of fat in the growing birds, and highfat content in the feed tempt to increase the weight of the liver in birds. In the current experiment, there was no significant difference (p < 0.05) in liver weight between all the groups, which is consistent with Lee et al [39], proposing that the addition of fermented feed ingredients into the broiler feed will preserve the normal immunity and health levels of the birds while preventing undesirable effects on the meat.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, the results of the current study did not show any treatment effect on the above-mentioned parameters. Moreover, Lee et al [39] reported that significantly higher WHC was in both breast and leg meat of chickens fed fermented soybean hulls which were confirmed by the result that FSBM3 improved the WHC by 10.99% compared to the control diet. It has been reported that ducks on a FSBM diet had lower pH values in the thigh and breast meat (p < 0.05), and the WHC of the breast meat 24 hours and 48 hours post mortem decreased by 11.26% and 8.21%, respectively [40], which contradicts the current study.…”
Section: Discussionmentioning
confidence: 76%
“…Water-holding capacity of meat is an important quality that is directly associated with tenderness, juiciness and influences the product output (Qiaofen Cheng and Da-Wen Sun, 2008;Warner, 2014;Lee et al, 2017;Mir Nasiret al, 2017). We did not establish significant changes of feeding amaranth on WHC and meat output after heat treatment which coincided with reports by researches on no effect of plant additives, including amaranth on water-holding capacity of rabbit meat (Alagónet al, 2015;Molina et al, 2018) Mancini et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…High protein and low fat contents as well as the high proportion of unsaturated fatty acids (PUFAs) are among the most popular demands from the consumers of broiler meats. Also, the yield and freshness of the meat are important factors affecting consumer preference (Lee et al, 2017;Marcinčák et al, 2018). Many studies revealed that the quality of broiler meats may substantially be affected by diets.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies revealed that the quality of broiler meats may substantially be affected by diets. With regard to the effect of fermented feed, Lee et al (2017) reported that feeding fermented soybean hulls resulted in higher contents of protein, lower fat and improved water holding capacity (WHC) of broiler breast meats. Likewise, Marcinčák et al (2018) noticed the improvements of oxidative status and the ratio of n-6/n-3 PUFAs in broiler meat with feeding fermented bioproduct.…”
Section: Introductionmentioning
confidence: 99%